Islam dan Sain: Telaah Terhadap Islamisasi Ilmu Pengetahuan dan Pengilmuan Islam - Kasori; Ikke Fitriana Nugrahini; Aulia Arsinta (4, 2024)
This article discusses the Relations of Islam and Science by examining the Islamization of Science Syed Muhammad al-Naquib al-Attas, Kuntowijoyo Islamic Studies and the Paradigm of Interconnection Integration-Transintegration of Science Amin Abdullah. The method used in this research is descriptive-qualitative method, and is included in the literature research. The process of collecting data in this study is by observing, in the sense of tracking various references that have relevance regarding the focus of the study, both from books, articles, and so on that function to support these data. The data analysis technique used in this research is the content analysis method. From the studies conducted, it can be seen that First, there are two similarities between the Islamization of science, Islamic scholarship and the trans-integration of knowledge, namely both being an Islamic response to the development of science and both rejecting secularism. Second, the difference between the Islamization of knowledge, Islamic scholarship and the transtegration of knowledge lies in the emphasis and details of the key concepts. The Islamization of science places more emphasis on Islam, Islamic scholarship places more emphasis on science, while the integration of interconnections tends to be more balanced in seeing the relationship between Islam and science. Third, the difference between the Islamization of knowledge, Islamic scholarship and the transtegration of knowledge occurs because of differences in background between the three. The Islamization of knowledge was initiated by people who were traumatized by colonialism, while Islamic scholarship and the transtegration of knowledge were not. Abstrak Artikel ini membahas tentang Relasi Islam dan Sains dengan mengkaji Islamisasi Sains Syed Muhammad al-Naquib al-Attas, Kajian Islam Kuntowijoyo dan Paradigma Integrasi Interkoneksi— Transintegrasi Sains Amin Abdullah. Metode yang digunakan dalam penelitian ini adalah metode deskriptif-kualitatif, dan termasuk dalam penelitian kepustakaan. Proses pengumpulan data dalam penelitian ini adalah dengan cara observasi, dalam arti menelusuri berbagai referensi yang mempunyai relevansi mengenai fokus penelitian, baik dari buku, artikel, dan lain sebagainya yang berfungsi untuk mendukung data tersebut. Teknik analisis data yang digunakan dalam penelitian ini adalah metode analisis isi. Dari kajian yang dilakukan terlihat bahwa Pertama, terdapat dua kesamaan antara Islamisasi ilmu pengetahuan, keilmuan Islam dan transintegrasi ilmu pengetahuan, yaitu keduanya merupakan respon Islam terhadap perkembangan ilmu pengetahuan dan sama-sama menolak sekularisme. Kedua, perbedaan Islamisasi ilmu, keilmuan Islam, dan transintegrasi ilmu terletak pada penekanan dan rincian konsep-konsep kuncinya. Islamisasi ilmu pengetahuan lebih menekankan pada Islam, keilmuan Islam lebih menekankan pada ilmu pengetahuan, sedangkan integrasi interkoneksi cenderung lebih seimbang dalam melihat hubungan antara Islam dan ilmu pengetahuan. Ketiga, perbedaan Islamisasi ilmu, keilmuan Islam, dan transintegrasi ilmu terjadi karena perbedaan latar belakang ketiganya. Islamisasi ilmu pengetahuan diprakarsai oleh masyarakat yang trauma dengan kolonialisme, sedangkan keilmuan Islam dan transintegrasi ilmu pengetahuan tidak.